Analysis of Various Performance Measurement Parameters (PMP) of Load Balancing Algorithms Used in Public Cloud Environment - Tiwari, Mangal Nath; Salimath, Nagesh; Sullare, Vijay Anand (International Journal of Computer Sciences and Engineering, 2023)
Cloud computing is on demand and hosted solution mechanism on the internet which provides the facilities to the individual and industry to use needed infrastructure and application via Internet. It reduces infrastructure setup cost of resources and offers cost efficiency, scalability, availability, reliability and flexibility. Cloud computing offers a competitive edge over your competitors, in this way cloud services helps the users to access the latest applications any time without spending time and money on installing and mainlining hardware and software resources [1]. Load balancing is a technique in which load balancers are responsible to manage and maintain the workload on the back end servers, It also offer the mechanism to distribute the workload across the servers evenly in such a way that no any server is found under loaded or overloaded. Load balancing improves application responsiveness and overall system performance. In this paper, an attempt has been made to study a few of the existing performance measurement matrices of load balancers that distribute the workload across the back end servers and also analyse the various performance metrics that affect the load balancing process. The load balancer applies several load balancing algorithms to determine the appropriate resources. However, it faces several problems while distributing the load across the available resources. The main objective and motivation of this paper is to do a comparative study of different types of existing performance measurement matrices that are used by load balancer to manage the workload distribution task in cloud computing environment.